Be(com)ing other-oriented : The value of mindfulness for leaders and leadership development - Urrila, Laura (Vaasan yliopisto, 2022)
This dissertation investigates how mindfulness may help leaders tap into their other-orientation. This dissertation consists of three papers which contribute to literature on mindfulness and leadership by increasing the understanding of how mindfulness learning may support leaders in social relations, in their role of leading others. Taking a qualitative longitudinal intervention approach, this dissertation examines the experiences of leaders who participated in a mindfulness training program. The data for analysis were collected from 62 leaders. Materials comprise 62 written pre-intervention assessments and 62 post-intervention interviews. First, this dissertation integrates prior knowledge of the implications of leaders’ mindfulness interventions and practices, positioning the research on leader mindfulness within leadership development, and clarifying mindfulness as a value-based developmental practice and interpersonal phenomenon. Second, the empirical findings highlight the potential significance of mindfulness for increasing social leadership capacity. This work builds an understanding of how mindfulness learning and practice foster the development of leaders’ social awareness across the dimensions of other-oriented thought, emotion, and behavior. Third, this dissertation builds a bridge between mindfulness and servant leadership by advancing understanding of how mindfulness-trained leaders engage in servant leadership behaviors while integrating mindfulness into their leadership work to develop themselves and to serve their followers and teams. Fourth, this dissertation provides insight into developmental pathways with the potential to build leaders’ capacity for other-oriented leadership by demonstrating how mindfulness training helps leaders develop through a combination of a formal program and continuous self-development, and holistically instead of providing training in specific skills. The findings are particularly useful for HR managers and development professionals evaluating and selecting leader development interventions.

Tässä väitöskirjassa selvitetään, kuinka ’mindfulness’ eli ’tietoinen läsnäolo’ (suomeksi myös ’hyväksyvä tietoinen läsnäolo’, ’läsnäolevuus’, ’mielellisyys’, ’tietoisuustaidot’) voi auttaa johtajia kehittymään toiseen suuntautuvassa johtajuudessa. Väitöskirjaan kuuluu kolme artikkelia, jotka tuottavat uutta tietoa mindfulness- ja johtajuuskirjallisuuteen lisäämällä ymmärrystä tietoisen läsnäolon merkityksestä johtajan sosiaalisten suhteiden tukena, ihmisten johtajina. Väitöskirjassa tutkitaan 62 mindfulness-koulutukseen osallistuneen johtajan kokemuksia laadullisen ja pitkittäisen interventiotutkimuksen keinoin. Aineisto käsittää 62 kirjallista ennakkotehtävää ja 62 intervention jälkeistä haastattelua. Ensiksi tämä väitöskirja kokoaa yhteen aiemman tutkimustiedon mindfulness-interventioiden ja -harjoitteen vaikutuksista johtajiin. Se asemoi johtajia koskevan mindfulness-tutkimuksen johtajuuden kehittämisen kenttään ja selkeyttää mindfulnessin käsitettä arvopohjaisena ja kehityksellisenä harjoitteena sekä ihmisten välisessä vuorovaikutuksessa esiintyvänä ilmiönä. Toiseksi tutkimuksen empiiriset löydökset vahvistavat tietoisen läsnäolon tärkeyttä sosiaalisen johtajuuskyvykkyyden kehittymiselle. Tutkimus lisää ymmärrystä siitä, kuinka mindfulness-osaaminen edistää johtajien sosiaalisen tietoisuuden kehittymistä kattaen toiseen suuntautuvan ajattelun, tunteen ja toiminnan ulottuvuudet. Kolmanneksi väitöskirja rakentaa siltaa mindfulnessin ja palvelevan johtamisen välille tarjoamalla tietoa mindfulness-koulutuksen käyneiden johtajien palvelevan johtamisen käytännöistä heidän soveltaessaan mindfulness-oppeja johtamistyössä hyödyttääkseen johdettaviaan. Neljänneksi väitöskirja tarjoaa näkemyksiä kehityspoluista, joiden kautta johtajuus voi rakentua yhä toiseen suuntautuvammaksi, näyttämällä kuinka mindfulness-koulutus auttaa johtajia kehittymään muodollisen kehittämisohjelman ja jatkuvan omaehtoisen itsensä kehittämisen yhdistelmän keinoin, sekä kokonaisvaltaisesti tiettyjen yksittäisten taitojen kehittämisen sijasta. Löydökset ovat erityisen hyödyllisiä johdon kehittämisinterventioita valitseville HR-päälliköille ja kehittämisammattilaisille.
Keywords: tietoinen läsnäolo; johtaminen; johtajuus; vuorovaikutus; tietoisuus; mietiskely; stressinhallinta; johtajat; rentoutus; työelämä; fi=Henkilöstöjohtaminen|en=Human Resource Management|